(untitled) (Applied Biological Research, 2016)
Occupational level greatly influences the physical activity which, in turn, significantly affects body composition and overall health. Ninety adult male participants in age group of 40-50 years from three occupational categories i.e. field workers, laboratory workers and office workers were selected from PAU, Ludhiana (India). The study revealed that higher income and education were positively and significantly (p≤0.01) correlated with body weight (r = 0.53; 0.48), BMI (r = 0.4; 70.44), waist circumference (r = 0.65; 0.58) and fat mass (r = 0.37; 0.34), respectively. Of the various activities carried out by participants, cycling and agricultural activities showed a significant but negative relation with body weight (r = -0.41, -0.86), BMI (r = -0.25, -0.38), waist circumference (r = -0.62; -0.37) and fat mass (r = -0.39; -0.27) while positively significant relationship was found with fat free mass (r = 0.31, 0.20). Body fat accumulation was positively and significantly correlated with body weight, BMI, waist circumference and fat mass, however, it was proteins which had significant enhancing effect on fat free mass (r = 0.29). Therefore, it may be concluded that physical activity is a leading factor that influences the anthropometry and body composition.